Numerical Modeling the Effect of Operating Variables on Faraday Efficiency in PEM Electrolyzer. (2016) - Tijani, Alhassan Salami; Rahim, A.H. Abdol
Abstract: In PEM water electrolysis, extensive mixing of the product gases due to gas crossover could produce explosive conditions and also at low current densities this leads to efficiency losses due to reduced Faraday efficiency. In this study, the effect of different temperatures, pressures and membrane thicknesses on the performance of a PEM electrolyzer have been carried out. The effect of membrane thickness on voltage was not apparent at lower current density but it increases from current density of 0.2A/cm 2 . It was also observed that temperature has no effect on the Faraday efficiency. On the other hand, Faraday efficiency increases as the current density increase. Also Faraday efficiency decreases with decrease in membrane thickness At 0.2 A/cm 2 current density and membrane thickness of 150 μm.